AB0799 Sex Influence on Psoriatic Disease Clinical and Therapeutic Features: Analysis of Real-Life Data From 3.560 Patients. (9th June 2015) - Generali, E.; Selmi, C.
Abstract : Background: Psoriatic disease, including skin psoriasis (Pso) and psoriatic arthritis (PsA), affects men and women with equal frequency but the influence of sex on clinical features [1], methotrexate (MTX) treatment [2], and survival has not been investigated in real-life settings. Objectives: To evaluate differences between sexes for age at diagnosis, age at initiation of MTX therapy, disease duration, MTX retention rate, and mortality in a large cohort of real life patients. Methods: We identified cases of Pso and PsA diagnosed between 2004-2013 in an administrative database through the research of disease specific copayment waivers that are assigned by physicians usually at the diagnosis of chronic diseases. Cases were then linked to MTX prescriptions, using the specific anatomical therapeutic chemical (ATC) code. Survival analyses were performed as of January 1st, 2013. The influence of demographic, clinical and therapeutic factors on drug survival was evaluated in men and women using the Cox-proportional hazard model and the results are presented as hazard ratio (HR) and 95% confidence interval (95%CI). Mortality is represented using Kaplan-Meier survival estimates. Results: We identified 761 patients affected by Pso (women 50%) and 2.799 patients affected by PsA (women 53%). Baseline demographics showed that age at diagnosis was significantly older in women for PsA (55.6±12.5 years in women vs. 53.1±12.7 in men, p <0.0001), but not Pso (women 57.9±14.1 years in women vs. 56.2±14.5 in men, p =0.0629). Disease duration did not differ significantly between women and men for both PsA (3.97±3.85 years in women vs. 3.69±3.85 years in men) and Pso (3.47±4.53 years in women vs. 3.82±4.42 years in men). MTX was prescribed to 48% (363/761) of Pso and 77% (2.168/2.799) PsA cases while, more importantly, it was prescribed significantly less frequently in women with Pso (42% vs. 58% in men; p <0.0001) and with similar frequency in patients with PsA of both sexes (50.7% vs. 49.3%). Interestingly, MTX was started at a significant older age in women with PsA (55.2±12 years in women vs. 51.2±12.5 years in men, p <0.0001) and PsO (56±13.1 years in women vs. 53±13.2 in men, p =0.02). The age at the first prescription of MTX was also significantly associated with drug survival, with an adjusted HR of 1.02 (95%CI 1.01-1.03, p =0.001). Unadjusted mortality rates did not differ significantly between men and women with Pso or PsA combined (Figure 1 ). Conclusions: Women are significantly older at the diagnosis of PsA and at the initiation of MTX therapy, while manifesting lower drug survival compared to men. The different magnitude of sex-related discrepancies between men and women with Pso or PsA may suggest that the articular manifestations of disease and our therapeutic approach may be significantly influenced by sex. References: Eder, L., et al., Gender difference in disease expression, radiographic damage and disability among patients with psoriatic arthritis. Ann Rheum Dis, 2013. 72(4): p. 578-82. Coates, L.C., A. Kavanaugh, and C.T. Ritchlin, Systematic review of treatments for psoriatic arthritis: 2014 update for the GRAPPA. J Rheumatol, 2014. 41(11): p. 2273-6. Disclosure of Interest: None declared